INCREASE MIGRATION OF PERIPHERAL BLOOD DERIVED ENDOTHELIAL PROGENITOR CELLS OF STABLE CORONARY ARTERY DISEASE PATIENT WITH ANGIOTENSIN CONVERTING ENZYME INHIBITORS - Achmad, Hanang Anugrawan; Oktaviano, Yudi Her; Soemantri, Djoko (Stem Cell Research and Development Center, Universitas Airlangga, 2023)
This research is based on refractory angina pectoris, which remains a problem despite advances in coronary heart disease treatment. Stem cell therapy is still in preclinical research stages to address refractory angina. Endothelial progenitor cells (EPCs) aid in improving endothelium and the growth of new blood vessels. Heart medication has shown to enhance both the quantity and function of EPCs in patients at cardiovascular risk or with heart disease. Previous studies reported that ACE inhibitors (ACEI) have a positive effect on EPCs. Thus, this study analyzes the impact of three different ACE inhibitors on EPC migration in laboratory conditions. Its aim is to ascertain the increase in EPC migration in stable coronary heart disease patients after ACEI administration. The research methodology involves an experimental design with a control group and post-treatment assessment only. Mononuclear cells are isolated from stable coronary heart disease patients' peripheral blood and incubated for 3 days. The EPCs are then divided into captopril, ramipril, lisinopril, and a control group, observed for 48 hours. EPC migration is assessed by counting the cells moving from the upper chamber to the membrane facing the lower chamber using a transwell migration assay after 20 hours, observed with a light microscope and Giemsa staining. Data analysis via ANOVA statistical tests indicates increased EPC migration in the captopril, ramipril, and lisinopril groups compared to the control. Captopril shows the highest effect among the groups, while no significant difference is observed between captopril and lisinopril, as well as between ramipril and lisinopril.